Polyvinylpyrrolidone-Capped Silver Nanoparticle Inhibits Infection of Carbapenem-Resistant Strain of Acinetobacter baumannii in the Human Pulmonary Epithelial Cell - Tiwari, Vishvanath; Tiwari, Monalisa; Solanki, Vandana (Frontiers in Immunology, 2017)
Acinetobacter baumannii, an opportunistic ESKAPE pathogen, causes respiratory and urinary tract infections. Its prevalence increases gradually in the clinical setup. Pathogenicity of Acinetobacter is significantly influenced by its ability to infect and survive in human pulmonary cells. Therefore, it is important to study the infection of A. baumannii in human pulmonary host cell (A-549), monitoring surface interacting and internalized bacteria. It was found that during infection of A. baumannii, about 40% bacteria adhered to A-549, whereas 20% got internalised inside pulmonary cell, and induces 3 fold increase in the ROS production. We have synthesized PVP capped AgNPs using chemical methods and tested its efficacy against carbapenem resistant strain of A. baumannii. PVP-AgNPs (30µM) have shown anti-bacterial activity against carbapenem resistant strain of A. baumannii and this concentration does not have any cytotoxic effect on the human pulmonary cell line (IC50 is 130µM). Similarly, PVP-AgNPs treatment decreases 80% viability of intracellular bacteria; decreases adherence of A. baumannii to A-549 (40 to 3%), and decreases intracellular concentration (20 to 1.3%) of A. baumannii. This concludes that PVP-capped silver nanoparticles (PVP-AgNPs) can be developed as a substitute for carbapenem to control the infection caused by carbapenem resistant A. baumannii.